Facilitating transcatheter aortic valve implantation in the era of COVID-19: Recommendations for programmes. (1st August 2020) - Lauck, Sandra; Forman, Jacqueline; Borregaard, Britt; Sathananthan, Janarthanan; Achtem, Leslie; McCalmont, Gemma; Muir, Douglas; Hawkey, Marian C; Smith, Amanda; Højberg Kirk, Bettina; Wood, David A; Webb, John G
Abstract: The COVID-19 pandemic continues to significantly impact the treatment of people living with aortic stenosis, and access to transcatheter aortic valve implantation. Transcatheter aortic valve implantation (TAVI) programmes require unique coordinated processes that are currently experiencing multiple disruptions and are guided by rapidly evolving protocols. We present a series of recommendations for TAVI programmes to adapt to the new demands, based on recent evidence and the international expertise of nurse leaders and collaborators in this field. Although recommended in most guidelines, the uptake of the role of the TAVI programme nurse is uneven across international regions. COVID-19 is further highlighting why a nurse-led central point of coordination and communication is a vital asset for patients and programmes. We propose an alternative streamlined evaluation pathway to minimize patients' pre-procedure exposure to the hospital environment while ensuring appropriate treatment decision and shared decision-making. The competing demands created by COVID-19 require vigilant wait list management, with risk stratification, telephone surveillance and optimized triage and prioritization. A minimalist approach with close scrutiny of all parts of the procedure has become an imperative to avoid any complications and ensure patients' accelerated recovery. Lastly, we outline a nurse-led protocol of rapid mobilization and reconditioning as an effective strategy to facilitate safe next-day discharge home. As the pandemic abates, TAVI programmes must facilitate access to care without compromising patient safety, enable hospitals to manage the competing demands created by COVID-19 and establish new processes to support patients living with valvular heart disease.